INFLUENCE OF THE "IMMOBILITY" FACTOR ON THE LEVELS OF PHYSICAL FITNESS AND THE STATE OF HEALTH OF STUDENTS - Shilko V.G. ,; Guseva N.L. ,; Sharafeeva A.B. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the impact of the “immobility” factor (due to the two-year period of online learning due to the COVID-19 pandemic) on the indicators of physical fitness and the health status of students. Methods and structure of the study. A comparative analysis of indicators of physical fitness and health status of 1st-3rd year students of 20 faculties and institutes of the National Research Tomsk State University was carried out in the pre-pandemic period (2019), as well as after its completion and the return of students to full-time education in the disciplines "Physical culture and sports "and" Elective disciplines in physical culture and sports " (2022). Results and conclusions. As the results of the study showed, the factor of forced "immobility" of students during the two-year period of study had a negative impact on the motivational sphere of students (men and women) in relation to physical culture and sports activities. Thus, in the first semester of the 2022-2023 academic year, the attendance of classes in the academic disciplines "Physical Culture and Sports" and "Elective Disciplines in Physical Culture and Sports", which were held in accordance with the schedule, decreased by 20% in general. And the quantitative indicator of the participation of NR TSU students in sports events decreased by almost one third, compared with the pre-pandemic period of study [4]. The low level of students' physical fitness is also confirmed by the results of testing the standards of the GTO complex.